Distribution and impact of the Asian seed beetle, Megabruchidius tonkineus (Pic, 1904) (Coleoptera: Chrysomelidae: Bruchinae) on Gleditsia triacanthos L. seeds in South Africa - Salgado, Sara; Martin, Grant (African Entomology, 2023)
Honey locust, Gleditsia triacanthos (Fabaceae) is a fast-growing deciduous tree native to North America. The tree has been introduced worldwide and has become invasive in South Africa. In 2017, it was listed as one of the nine fastest-spreading weeds in South Africa. Once established, it competes with and displaces indigenous species and dense stands can significantly reduce stream flow. The Asian seed-feeding bruchid, Megabruchidius tonkineus (Coleoptera: Chrysomelidae: Bruchinae) was introduced into South Africa and has subsequently taken honey locust as a host plant. The beetle damages honey locust seeds and is therefore considered a biological control agent, despite no host-specificity or impact studies having been conducted. This study shows that M. tonkineus has established across the entire G. triacanthos population range in South Africa, damaging approximately 9% of seeds. Laboratory studies show that M. tonkineus completes its larval development in the seeds of G. triacanthos in about 66.80 ± 0.69 SE days before emerging. This study is the first to describe the distribution and impact of this alien insect in South Africa.